The Effect of Student Leader Training on Developing Media Learning Process - Bunga-mongkon, Nit; Kotwan, Utumporn (Ratchaphruek Journal, 2020)
The objective of this research was to study the findings in students leader training for developing the media literacy. The research methodology was divided into 2 Phases. Phase 1: Surrey the level media literacy from 400 students selected by using random sampling. Using media Literacy Scale, the study found that the samples’ knowledge level in media literacy was in “High” level. However, based on item analysis, it found that some parts of their knowledge level were in “Moderate” level. Then, the 30 students with “Moderate” level and lower scores with volunteer to be the participants were selected to be sample in the Phase 2. The research instrument was the Training Program for Student Leader. The research was found that the samples’ post-test mean value of media literacy was higher than the pre-test at .05 significant level.